Agreeing inflected quantifiers, intensifiers and anaphors as derived personal pronouns: Evidence from Tatar. (September 2022) - Lyutikova, Ekaterina
Abstract : In this paper, I analyse the intricate agreement pattern attested with inflected quantifiers, intensifiers and anaphors in Tatar, which can trigger not only a default 3 rd person agreement, but also the marked person agreement reflecting the features of their restrictor or binder. I claim that in these constructions, inflected quantifiers, intensifiers and anaphors bear the features the agreement reveals, and propose a mechanism allowing them to acquire the features of their restrictor or binder. I build on the idea that agreeing inflected quantifiers, intensifiers and anaphors contain a minimal pronoun equipped with a set of unvalued interpretable features, and that this feature set gets valued via agreement.